A WISE FINANCIAL CONTROL PROGRAM TO IMPROVE THE FINANCIAL STABILLITY OF CHICKEN SEMPOL MICRO AND SMALL ENTERPRISES(MSEs) - Silvian G. Pattiasina; Ilham N. Bugis; Pauji Tasalisa (PT. Jurnal Center Indonesia Publisher, 2026)
Micro and Small Enterprises (MSEs) play an important role in supporting local economic development; however, many MSE actors still face challenges in managing their business finances effectively. Common problems include the absence of systematic financial records, the mixing of personal and business finances, and limited understanding of financial control. This community service program aimed to improve the financial literacy and financial management practices of the Sempol Ayam Micro and Small Enterprise through an educational and mentoring-based approach. The program was implemented through counseling, training, and direct mentoring focusing on daily transaction recording, cash flow management, production cost calculation, and the preparation of simple profit and loss statements. The results indicate a significant improvement in the partner’s financial management practices, including more systematic bookkeeping, clearer separation of personal and business finances, more accurate cost calculations, and better monitoring of business performance. Overall, the program contributed positively to enhancing financial control, financial stability, and business sustainability of the micro-enterprise. These findings demonstrate that simple and practical financial management assistance can effectively strengthen the capacity of Micro and Small Enterprises.